Disclosure of environmental information in China - Lang, Dezhong (Pub KSU, 2014)
This article contains information about the availability of information on the State of the environment for the citizens of China. Access to environmental information was officially guaranteed in China in 2008, «the interim order the disclosure of environmental information, and since then efforts of many environmental NGOS aim to make this mechanism work. Institute of public policy collects official information on enterprisespollutants and impurities and represents it on the site map pollution». In this organization now more than 80000 records, they also publish a variety of analytical work
Қытайдың қоршаған ортасының жағдайы туралы ақпаратты ашып көрсету
Раскрытие информации о состоянии окружающей среды Китая
Keywords: information; commercial secrets; administrative organ; pollution information transparency index (PITI); political; production technology